Dietade lithobates zweifelihillis, frost y webb 1984 (anura: ranidae) en un río estacional del Centro de México - Mendoza-Estrada, Luís Javier; Lara López, Rosmandi; Castro-Franco, Rubén (Instituto de Ecología, A.C., 2008)
The diet of Lithobates zweifeli was studied by means of stomach flushing in a seasonal river of Morelos, Mexico. Diet was analyzed by season (wet and dry), development stages and by sex. Food items were classified by their habits in terrestrial or aquatic prey, and determined to order, family, genus and sometimes to species. The diet of L. zweifeli comprised 102 nutritional components, mainly land habits insects. Hemiptera (Cicadellidae), Lepidoptera (Noctuidae) and Megaloptera (Corydalus texanus) had the highest values of ingestion and frecuence in the diet. We found 54 nutritional components in the dry season, and 84 in the rainy season. The estimated amplitude of trophic niche by the Levin’s method revealed low values in both seasons. Diet was constituted by 63 nutritional components in females, 55 in males and 49 in juveniles. A Chi-squared test showed not significant differences in the diet by development stage, sex, and season. The overlap of the trophic niches estimated by the MacArthur and Levin index revealed low value in sex and season combinations. The floating and riparian vegetation as insects´ habit is important for the feeding of L. zweifeli.